2021
DOI: 10.1039/d1cp02829d
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization and methane activation on SnOx/Cu2O/Cu(111) inverse oxide/metal catalysts

Abstract: To activate methane at low or medium temperatures is a difficult task and a pre-requisite for the conversion of this light alkane into high value chemicals. Herein, we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 58 publications
4
51
0
Order By: Relevance
“…This finding demonstrates the relevant role played by an inverse ZnO/Cu configuration . In subsequent works, a substantial enhancement in the rate of methanol synthesis on Cu(111) was found after growing islands of zinc oxide onto this substrate. , In a ZnO/Cu configuration, the oxide overlayer and the oxide-metal interface have structural and electronic properties not seen for a regular Cu/ZnO configuration. ,, In general, the dispersion of oxide nanoparticles (ZnO, TiO 2 , SnO 2 , CeO 2 ) on a Cu(111) substrate generates very good catalysts for C1 chemistry (CO and CO 2 conversion, methanol synthesis, forward and reverse water–gas shift reactions, methane activation). …”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…This finding demonstrates the relevant role played by an inverse ZnO/Cu configuration . In subsequent works, a substantial enhancement in the rate of methanol synthesis on Cu(111) was found after growing islands of zinc oxide onto this substrate. , In a ZnO/Cu configuration, the oxide overlayer and the oxide-metal interface have structural and electronic properties not seen for a regular Cu/ZnO configuration. ,, In general, the dispersion of oxide nanoparticles (ZnO, TiO 2 , SnO 2 , CeO 2 ) on a Cu(111) substrate generates very good catalysts for C1 chemistry (CO and CO 2 conversion, methanol synthesis, forward and reverse water–gas shift reactions, methane activation). …”
Section: Introductionmentioning
confidence: 72%
“…The AP-XPS measurements were done using a SPECS instrument equipped with a PHOIBOS 150 EP MCD-9 analyzer and a Mg Kα X-ray source. 13,15,19 The experiments examining the catalytic activity of the ZrO 2 /CuO x /Cu(111) systems were performed in a setup that combines an ultrahigh vacuum (UHV) chamber for surface characterization and a batch microreactor for catalytic tests. 13,15,17 The UHV chamber was equipped with instrumentation for XPS (Al/Mg K alpha), Auger electron spectroscopy (AES), ion-scattering spectroscopy (ISS), and temperature-programmed desorption (TDS).…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sn and SnO x have been studied and employed in the past for use as gas sensors and are used in diverse types of catalytic reactions such as ethanol oxidation for fuel cells, CO oxidation, electrochemical CO 2 reduction, dry reforming and steam reforming of methane, partial oxidation of methane, and methane chlorination. Additionally, in a previous study, our group investigated methane activation on highly dispersed SnO x nanoparticles (NPs) that were grown on Cu 2 O/Cu­(111) using reactive deposition . This study demonstrated that SnO x /CuO x /Cu­(111) catalysts activate methane even at room temperature and enhance the activity upon creation of a SnO x –Cu 2 O interface . However, the contribution of pure SnO x without any interfacial sites cannot be distinguished by such a system due to the existence of an active SnO x –Cu 2 O interface.…”
Section: Introductionmentioning
confidence: 99%
“…They are more conductive , and more resistant to electromigration . They can serve as a platform for investigating catalytic mechanisms and enhancing catalytic performance and also for growing epitaxial foreign materials such as graphene and transition metal dichalcogenides. Specific interest has been placed on the (111) orientation. Rodriguez et al reported that TiO 2– x /Au­(111) and CeO 2– x /Au­(111) catalysts shows high water–gas shift performance .…”
Section: Introductionmentioning
confidence: 99%